Wave Attenuation and Gas Exchange Velocity in Marginal Sea Ice Zone. Issue 3 (30th March 2018) - Bigdeli, A.; Hara, T.; Loose, B.; Nguyen, A. T.
Abstract: The gas transfer velocity in marginal sea ice zones exerts a strong control on the input of anthropogenic gases into the ocean interior. In this study, a sea state‐dependent gas exchange parametric model is developed based on the turbulent kinetic energy dissipation rate. The model is tuned to match the conventional gas exchange parametrization in fetch‐unlimited, fully developed seas. Next, fetch limitation is introduced in the model and results are compared to fetch limited experiments in lakes, showing that the model captures the effects of finite fetch on gas exchange with good fidelity. Having validated the results in fetch limited waters such as lakes, the model is next applied in sea ice zones using an empirical relation between the sea ice cover and the effective fetch, while accounting for the sea ice motion effect that is unique to sea ice zones. The model results compare favorably with the available field measurements. Applying this parametric model to a regional Arctic numerical model, it is shown that, under the present conditions, gas flux into the Arctic Ocean may be overestimated by 10% if a conventional parameterization is used. Key Points: Reduction of air‐sea gas exchange in limited waters Sea ice as enhancers or inhibitors of effective gas exchange in marginal sea ice zones Sea ice role in parameterization of gas exchange based on turbulence kinetic energy dissipation